Occurrence and intensity of tick infestation on stray dogs in Kelantan and Selangor - Lye Yi Yan (2022)
The close relationship of dogs with humans has raised concerns about the spread of potential zoonotic diseases that can be transmitted through ectoparasites such as ticks. Hence, the occurrence and intensity of tick infestation on stray dogs with risk factors of age, sex, neutering status, state, and body section of stray dogs were examined because of their high possibility to be in contact with human, or in contact with house dogs that have closer associations with humans thus facilitate the transmission of zoonotic disease to human via ticks. It was important to determine the predilection sites of the ticks in this study to develop a strategic tick control program for dogs to prevent or reduce tick-borne disease in Malaysia. A total of 64 stray dogs from Kelantan and Selangor were examined via integumentary examination and a total of 431 ticks, constituting Rhipicephalus sanguineous and Haemaphysalis sp. were collected. The overall occurrence of tick infestation was 82.81% (53/64) and the intensity of tick infestation from stray dogs examined was 8.13 ticks (1 – 17 ticks) per stray dog. Risk factors such as neutering status and states were associated with tick infestation in this study. The most preferred site for ticks attachment were the head, ear, and neck. In conclusion, this study revealed the high occurrence and tick intensity on stray dogs in Malaysia which highlights the importance of implementing tick control programs on stray dogs that can serve as the potential risk for public health on tick-borne diseases. Keywords: Ixodidae, Occurrence, Tick intensity, Tick infestation, Risk factors, Stray Dogs